Exercises and techniques to improve the effectiveness of students’ as a future interpreter - Xalilova Guzal Abdupattahovna (Universal Teaching and Learning Journal, 2025)
Purpose: This article aims to examine exercises and techniques that enhance interpreters’ effectiveness by strengthening cognitive, linguistic, and practical skills. The study emphasizes the significance of active listening, memory retention, and quick decision-making in real-world interpreting contexts. Research methodology: A qualitative descriptive approach was employed, synthesizing insights from professional guidelines, theoretical frameworks, and practical training experiences. Various strategies such as memory enhancement exercises, shadowing techniques, and simultaneous interpretation drills were analyzed to determine their relevance and applicability. Results: The findings indicate that interpreters benefit significantly from consistent practice using diverse materials, including speeches, interviews, and real-time conversations. These practices improve fluency, accuracy, and the ability to manage stress under time pressure. Furthermore, combining theoretical knowledge with practical application reinforces professional communicative competence. Conclusions: Continuous professional development is essential for interpreters to maintain and advance their performance. Structured training, coupled with exposure to authentic communication scenarios, ensures both adaptability and long-term proficiency. Limitations: The study is conceptual and does not include empirical testing with a specific sample of interpreters, which limits generalizability. Future research should integrate experimental or longitudinal data to strengthen validation. Contribution: This article provides a comprehensive framework of exercises and strategies that can serve as a practical guide for interpreter training programs and individuals seeking to refine their professional competence.